(untitled) (Medicine Today, 2025)
Introduction: Breast cancer is the leading cause of cancer-related mortality among women worldwide. While the burden is rising in low- and middle-income countries, data on associated risk factors remain limited, particularly in Bangladesh. Aim of the study: This study aimed to identify and evaluate sociodemographic, anthropometric, lifestyle, and reproductive risk factors for breast cancer in Bangladeshi women attending tertiary care hospitals. Materials and Methods: Over one year, this prospective observational study investigated breast cancer risk factors among 85 women treated at the Department of Surgery, Khulna Medical College Hospital, Khulna, Bangladesh from June 2021 to July 2024. Ethical approval and informed consent were obtained. Participants met specific inclusion criteria, including histologically confirmed breast cancer and age ≥18, while those with other cancers, mental disorders, or chronic diseases were excluded. Data were collected via structured interviews and physical examinations, considering age, BMI, menarche, first live birth, family history, menopausal status, and prior breast surgery. SPSS 26.0 was used foranalysis, applying logistic regression to identify risk factor associations with statistical significance set at p<0.05. Result: Women aged >60 years had significantly lower odds of breast cancer (AOR: 0.40, 95% CI: 0.20–0.80, p=0.01) compared to those <39 years. Unemployment (AOR: 1.50, 95% CI: 1.00–2.30, p=0.05) and urban residence (AOR: 1.50, 95% CI: 1.00–2.30, p=0.05) were associated with higher risk. Overweight (BMI 25–29.9 kg/m²) and obesity (BMI ≥30 kg/m²) significantly increased the odds of breast cancer. Lifestyle factors, including diet, smoking, and alcohol intake, showed no significant associations, while physical activity demonstrated a potential protective effect. Conclusion: Sociodemographic and anthropometric factors, such as unemployment, urban residence, and higher BMI, were significantly associated with breast cancer risk in this population. Lifestyle and reproductive factors did not show strong associations. These findings highlight the need for targeted interventions to address modifiable risk factors and improve early detection strategies in Bangladesh. Medicine Today 2025, Vol.37 (2): 204-208